Preserving Local Wisdom: Unaizah's Coffee Culture and Dates Farming Sustaining Cultural Heritage - Kurniawan Arif Maspul; Fawaz Ali Almalki (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This article explores the profound significance of Unaizah's coffee culture and dates farming in sustaining the region's cultural heritage. It highlights the unique relationship between coffee shops and dates farms, emphasizing their role in sustaining the economy, society, and environment while safeguarding local wisdom. Unaizah, renowned for its dates farming and traditional coffee cultures, holds a prominent position in global agriculture. This article delves into the historical context, economic implications, societal dynamics, and ecological sustainability intertwined with Unaizah's coffee culture and dates farming. The findings unequivocally demonstrate the pivotal role of these practices in preserving local wisdom and cultural heritage, underscoring the importance of understanding and honoring Unaizah's distinctive traditions in an ever-changing world.